2019
DOI: 10.3389/fchem.2019.00291
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Aggregation-Induced Emission-Active Probe Enables in situ and Long-Term Tracking of Endogenous β-Galactosidase Activity

Abstract: High-fidelity tracking of specific enzyme activities is critical for the early diagnosis of diseases such as cancers. However, most of the available fluorescent probes are difficult to obtain in situ information because of tending to facile diffusion or inevitably suffering from aggregation-caused quenching (ACQ) effect. In this work, we developed an elaborated near-infrared (NIR) aggregation-induced emission (AIE)-active fluorescent probe, which is composed of a hydrophobic 2-(2-hydroxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 73 publications
(76 reference statements)
0
13
0
1
Order By: Relevance
“…5b ). 64 The results of the Cell experiment revealed that QM-HBT-βgal could realize long-term NIR fluorescence imaging in SKOV-3 cells. Considering the high performance of QM-HBT-βgal and QM-βgal, it was believed that the AIE-active strategy provides a new pathway to design enzyme-activatable probes for on-site sensing and long-term tracking in living samples.…”
Section: Aie-active Probes For On-site Sensing and Long-term Trackingmentioning
confidence: 98%
“…5b ). 64 The results of the Cell experiment revealed that QM-HBT-βgal could realize long-term NIR fluorescence imaging in SKOV-3 cells. Considering the high performance of QM-HBT-βgal and QM-βgal, it was believed that the AIE-active strategy provides a new pathway to design enzyme-activatable probes for on-site sensing and long-term tracking in living samples.…”
Section: Aie-active Probes For On-site Sensing and Long-term Trackingmentioning
confidence: 98%
“…In 2019, Guo et al reported a probe for monitoring β -gal activity, designed around the commonly used AIE quinoline–malononitrile fluorophore. 114 A 2-(2-hydroxyphenyl)benzothiazole moiety was conjugated to both increase lipophilicity and extend the π-system to favour NIR emission. A galactose residue was attached to the probe to act as the recognition moiety, to give the probe QM-HBT-βgal .…”
Section: Multiple Modality Fluorescent Probesmentioning
confidence: 99%
“…Thus, β-gal activity detection has been exploited with diverse techniques including colorimetric assays (James et al, 2000;Browne et al, 2010;Zeng et al, 2012;Yeung et al, 2013;Chen et al, 2016; Abbreviations: NMR, nuclear magnetic resonance; MRS, magnetic resonance spectroscopy; MRI, magnetic resonance imaging; TR, repetition time; TE, echo time; β-gal, β-galactosidase; FAC, ferric ammonium citrate, TBAB, tetrabutylammonium bromide; CH2Cl2, dichloromethane; HRMS, high-resolution mass spectrometry; PBS, phosphate-buffered saline; X-Gal, 5bromo-4-chloro-3-indolyl-β-D-galactopyranoside; S-Gal, 3,4-cyclohexenoesculetin β-D-galactopyranoside; DMSO, dimethyl sulfoxide; TLC, thin-layer chromatography. 2017), fluorescence (Tung et al, 2004;Urano et al, 2005;Josserand et al, 2007;Kamiya et al, 2007;Feng et al, 2009;Koide et al, 2009;Kamiya et al, 2011;Oushiki et al, 2012;Han et al, 2013;Sakabe et al, 2013;Lee et al, 2014;Asanuma et al, 2015;Peng et al, 2015;Zeng et al, 2015;Doura et al, 2016;Gu et al, 2016;Zhang C. et al, 2016;Zhang X. X. et al, 2016;Jiang et al, 2017;Kim et al, 2017;Nakamura et al, 2017;Wei et al, 2017;Zhang et al, 2017;Tang et al, 2017;Chen et al, 2018;Ito et al, 2018;Liu et al, 2018;Yang et al, 2018;Chen et al, 2019;Fu et al, 2019;Gu et al, 2019;…”
Section: Introductionmentioning
confidence: 99%